EFFECTIVE USE OF REGIONAL TOURISM’S POTENSIAL AND ITS ASSESSMENT METHODS (E Global Congress, 2023)
This article highlights the importance of effective use of regional tourism potential, its assessment directions and methods, and offers suggestions for effective use of assessment methods.